Novel mutation in the SLC12A3 gene in a Sri Lankan family with Gitelman syndrome & coexistent diabetes: a case report - Subasinghe, Chandrika Jayakanthi (BMC Nephrol, 2017)
BACKGROUND: Gitelman syndrome (GS) is a rare autosomal recessively inherited salt-wasting tubulopathy associated with mutations in the SLC12A3 gene, which encodes for NaCl cotransporter (NCC) in the kidney. CASE PRESENTATION: In this report, we describe two siblings from a Sri Lankan non-consanguineous family presenting with hypokalaemia associated with renal potassium wasting, hypomagnesemia, hypocalciuria and hypereninemic hyperaldosteronism with normal blood pressure. Genetic testing showed that both were homozygotes for a novel missense mutation in exon 10 of the SLC12A3 gene [NM_000339.2, c.1276A > T; p.N426Y], which has not previously been reported in the literature in association with GS. Their mother was a heterozygous carrier for the same mutation. The father was not alive at the time of testing. This novel mutation extends the spectrum of known SLC12A3 gene mutations and further supports the allelic heterogeneity of GS. Interestingly both siblings had young onset Diabetes with strong family history. CONCLUSION: These findings have implications in providing appropriate genetic counseling to the family with regard to the risk associated with inbreeding, the detection of carrier/presymptomatic relatives. It further expands the known spectrum of genotypic and phenotypic characteristics of Gitelman syndrome.